2019
DOI: 10.1111/zph.12555
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis E virus infection among people and swine in mainland China: A systematic review and meta‐analysis

Abstract: Hepatitis E virus (HEV) infection remains an important public health problem, and it is endemic primarily in developing countries. This study aimed to evaluate the seroprevalence of HEV among the general population, occupational population and swine in mainland China and its risk factors based on a systematic review and meta‐analysis. Systematic search from EMBASE, PubMed, Web of Science, Cochrane Library and several Chinese databases, such as Wanfang (WF) Data, China National Knowledge Infrastructure (CNKI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
4
14
4
Order By: Relevance
“…Our previous study has provided evidence of a far higher rate of anti-HEV IgG seroprevalence in the general population (31%) compared with an earlier study indicating a seroprevalence rate of 9% only [23, 26]. In addition, the seroprevalence of anti-HEV IgG and IgM in this study is slightly higher compared with a previous study observed in general and occupational populations in different parts of China [29]. This difference is attributable to the sensitivity of the ELISA test systems applied, which differ substantially with regard to their sensitivity [30, 31].…”
Section: Discussioncontrasting
confidence: 72%
“…Our previous study has provided evidence of a far higher rate of anti-HEV IgG seroprevalence in the general population (31%) compared with an earlier study indicating a seroprevalence rate of 9% only [23, 26]. In addition, the seroprevalence of anti-HEV IgG and IgM in this study is slightly higher compared with a previous study observed in general and occupational populations in different parts of China [29]. This difference is attributable to the sensitivity of the ELISA test systems applied, which differ substantially with regard to their sensitivity [30, 31].…”
Section: Discussioncontrasting
confidence: 72%
“…Together with the scarcity of clinical cases, hallmark of a low incidence, and the low proportion of HEV IgG antibodies previously reported in blood donors [11], the low seroprevalence (raw and weighted) observed herein suggest that Reunion Island is a low endemic area for HEV transmission. Few HEV seroepidemiological studies have been conducted within general populations, as compared to studies among blood donors [[15], [16], [17]]. The figures observed in our study are in strong contrast with the seroprevalence averaging 25% in hyperendemic industrialized countries from the northern hemisphere, including France, Germany, the Netherlands and China [15,17].…”
Section: Discussioncontrasting
confidence: 91%
“…Our findings confirm that males are at higher risk of HEV exposure, which has been observed both in other general populations [2,19,22] as in blood donors [11]. This might be related to occupational differences, as it has been shown that the gender effect is abrogated when the population is stratified by the occupation [17] or when the study is conducted within occupations at risk [18]. It may also be driven by ethnic/cultural differences on Reunion Island, as previously observed in the United States with the rising incidence among non-Hispanic Asian females, which has abrogated the male predominance in recent years [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…products and direct contact with infected animals (11)(12)(13)(14)(15). Most HEV infections are asymptomatic and self-limiting (16).…”
mentioning
confidence: 99%